The Correlations of Body Image, Eating Behavior Types, and Energy and Nutrient Adequacy Level with Anemia Status in Adolescent Girls at SMAN 1 Dramaga, Bogor Regency - Novi Puspita Sari; Lilik Kustiyah; Hadi Riyadi (Media Publikasi Cendekia Indonesia, 2026)
Anemia is a serious global public health issue with the highest prevalence in adolescent girls. This study aimed to analyze the relationships among body image, eating behaviour, and the adequacy of energy and nutrient intake with anemia status in adolescent girls. This study used a cross-sectional design with 105 participants selected through purposive sampling. Data on subject characteristics were collected using a questionnaire, body image was assessed using the Body Shape Questionnaire (BSQ), eating behaviour using the Dutch Eating Behaviour Questionnaire (DEBQ), nutrient adequacy level using 2 × 24 H food recall, and hemoglobin levels were measured using HemoCue 301. Data were analysed using the Spearman Rank test. The results showed that 28.6% of the subjects had anemia. Based on bivariate analysis, there was no correlation between body image and anemia status (r=-0.108, p =0.271). There was also no correlation between emotional eating, external eating, and restrained eating (p>0.05) and anemia status. Similarly, energy (r= 0.133, p=0.177), vitamin B9 (r=0.169, p=0.085), and vitamin C (r=0.016, p=0.873) were not significantly correlation with anemia status. However, adequacy level of protein (r=0.288, p=0.003), iron (r= 0.194, p=0.048), and vitamin B12 (r= 0.216, p=0.027) were significantly positive correlation with anemia status. This study indicates that the majority of subjects had a negative body image, tended to display external eating behavior, and generally had insufficient nutrient intake. Therefore, nutrition education for adolescents is needed, with a focus on promoting healthy and high-quality eating habits.